Zemahşerî Tefsirinde Emanet Âyeti - (:unkn) unknown (My University, 2016)
Ahzâb 33/72-73. âyetlerinde anlatılan "emanetin arz edilmesi" tefsir geleneğinde farklı şekillerde anlaşılmıştır. Önce Zeccâc (ö. 311/923), Matürîdî (ö. 333/944) ve Nehhâs (ö. 338/949) tarafından ifade edilen, daha sonra Zemahşerî (ö. 538/1143) tarafından delillendirilerek öne çıkarılan bir yorum, sonraki tefsir geleneği üzerinde çok etkili olmuş görünmektedir. Özellikle emanetin sunulması (arz) ve yüklenilmesine (haml) ilişkin ifadelerin mecaza hamledilmesi yaygın bir kabul görmüştür. Zemahşerî'nin yorumu, diğer yorumlar karşısında güçlü bir argümantasyona sahip olsa da kusursuz değildir. Bu yazıda âyetin tefsirindeki ihtilaf noktalarını özetledikten sonra Zemahşerî'nin yorumunda başarılı bir şekilde cevaplandırılmadığı düşünülebilecek soruları sormaya, meseleyi bu yönüyle tartışmaya çalışacağız

The expression of "offering the Trust" stated in the Quran, chapter alAhzab (The Joint Forces) 33/ 72-73, is interpreted divergently in the commentary tradition. One of the well-supported interpretation, which is first stated by Zajjaj (d. 311/923), Maturidi (d. 333/944) and Nahhas (d. 338/949) and supported by evidence by Zamakhshari, has been quite influential on the commentary tradition later on. Especially the relationship between the terms, "offering of the Trust" (are) and "undertaking it" (gaml) is most often taken as a metaphor. Although Zamakhshari's interpretation has a stronger argumentation than other interpretations, it is not flawless. In this article I am going to discuss difficulties inherent in Zamakhshari's interpretation. First, I am going to highlight issues of disagreement, then I am going to raise the questions that may not be satisfactorily answered by Zamakhshari's interpretation
Zamakhshari's Interpretation of the Qur'anic Verse of the "Offering the Trust"
Keywords: Din Bilimi